Pengaruh Manajemen Laba Terhadap Cost Of Equity Capital - Nia Yuniarsih (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
The objective of this study is to examine the influence of earings management, to cost of equity capital. This study takes sample from 47 companies in the manufacturing sector at the Indonesia Stock Exchange (IDX), which were published in financial report from 2012-2013. The sample was determined based on the following criteria: (a) the annual report ended 31 December, and (b) book value of equity is positive. Earnings management were measured by Modified Jones Model and cost of equity capital was estimated by Capital Asset Pricing Market. The research hypotheses were tested using single regression. The results of this research show that earnings management had positive significant influence on cost of equity capital.